AB0220 TENOSYNOVITIS AS THE PRESENTING FEATURE OF FLARE IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Rayner, F.; Kerrigan, S.; Dyke, B.; Mcgucken, A.; Maybury, M.; Filer, A.; Pratt, A.; Isaacs, J.
Abstract : Background: The importance and relevance of tenosynovitis (TS) has long been recognised in rheumatoid arthritis (RA), but it is not usually considered in disease activity assessments. The significance of TS in early arthritis (EA) has also been recognised and, using ultrasound (US) it has recently been identified as a precursor to RA 1 . The ongoing BIO-FLARE (BIOlogical Factors that Limit sustAined Remission in rhEumatoid arthritis) observational study aims to investigate the pathogenesis of flare in RA. Patients with RA in remission stop their disease modifying anti-rheumatic drug medication (DMARDs: methotrexate, sulfasalazine and/or hydroxychloroquine) and are closely followed for 6 months, in anticipation that approximately 50% will experience a flare. We investigated whether TS occurrence was a frequent herald of flare in this cohort. Objectives: To review the case notes of 49 patients in the BIO-FLARE study with confirmed flare to date, seeking evidence of US tenosynovitis prior to or concurrent with flare. Methods: Patients in the study who are deemed to be in remission based on a disease activity score (DAS28-CRP) < 2.4 stop their DMARD medication and attend regularly for review over 6 months, with provision for ad-hoc appointments if symptoms return between visits. Patients are defined as having a flare if their DAS28-CRP ≥ 3.2 at any point or two consecutive DAS28-CRP ≥ 2.4. Targeted US assessment occurs at baseline only for patients that consent to an optional baseline ultrasound-guided synovial biopsy. If a flare occurs, US of symptomatic joints is undertaken, to assess suitability for a synovial biopsy. Following this, the patient receives a steroid injection and restarts their DMARD medication. Results: To January 2020, 120 patients had been recruited into the study and 49 experienced a flare. Seven patients had a flare predominantly or initially characterised by TS or paratenonitis, the results of which are summarised in Table 1 . Conclusion: Although highlighted as a precursor of RA in early arthritis 1, the occurrence of TS in the context of flare – and the prodrome heralding this – has not been studied. Our findings show that TS in early flare is reminiscent of the features sometimes seen in EA or clinically suspect arthralgia 2 . Further data are required to determine the role of periarticular inflammatory phenomena, such as TS, as risk factors for joint synovitis. Our study did not entail formal US assessments, therefore the rate of TS in this population may be under estimated. Careful study of RA patients in early phase of disease flare may pose an opportunity to characterise the nature and chronology of this association in greater depth. References: [1 ]Sahbudin I et al. Rheumatology. 2018;57(7):1243-1252 [2 ]Mankia K et al. Ann rheum dis. 2019;78(6):781-786 Acknowledgments: The Research was funded by the Medical Research Council and supported by NIHR Newcastle Biomedical Research Centre Disclosure of Interests: Fiona Rayner: None declared, Sean Kerrigan: None declared, Bernard Dyke: None declared, Andrew McGucken: None declared, Mark Maybury: None declared, Andrew Filer: None declared, Arthur Pratt Grant/research support from: Pfizer, GlaxoSmithKlein, John Isaacs Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Gilead, Janssen, Merck, Pfizer, Roche